Temperature-induced increase in methane release from peat bogs: a mesocosm experiment. - Julia F van Winden; Gert-Jan Reichart; Niall P McNamara; Albert Benthien; Jaap S Sinninghe Damsté (PLoS ONE, 2012)
Peat bogs are primarily situated at mid to high latitudes and future climatic change projections indicate that these areas may become increasingly wetter and warmer. Methane emissions from peat bogs are reduced by symbiotic methane oxidizing bacteria (methanotrophs). Higher temperatures and increasing water levels will enhance methane production, but also methane oxidation. To unravel the temperature effect on methane and carbon cycling, a set of mesocosm experiments were executed, where intact peat cores containing actively growing Sphagnum were incubated at 5, 10, 15, 20, and 25°C. After two months of incubation, methane flux measurements indicated that, at increasing temperatures, methanotrophs are not able to fully compensate for the increasing methane production by methanogens. Net methane fluxes showed a strong temperature-dependence, with higher methane fluxes at higher temperatures. After removal of Sphagnum, methane fluxes were higher, increasing with increasing temperature. This indicates that the methanotrophs associated with Sphagnum plants play an important role in limiting the net methane flux from peat. Methanotrophs appear to consume almost all methane transported through diffusion between 5 and 15°C. Still, even though methane consumption increased with increasing temperature, the higher fluxes from the methane producing microbes could not be balanced by methanotrophic activity. The efficiency of the Sphagnum-methanotroph consortium as a filter for methane escape thus decreases with increasing temperature. Whereas 98% of the produced methane is retained at 5°C, this drops to approximately 50% at 25°C. This implies that warming at the mid to high latitudes may be enhanced through increased methane release from peat bogs.